Expert System to Diagnose Diabetes Using Web-Based Fuzzy Mamdani Method: Expert System to Diagnose Diabetes Using Web-Based Fuzzy Mamdani Method - Mohammad Alfiandy; Iwan Wahyudin; Winarsih Winarsih (Institute of Computer Science (IOCS), 2020)
The aim of the system maker is to diagnose diabetes using a web-based fuzzy Mamdani method that is useful for detecting diabetes. Diabetes is also diabetes or diabetes. If the disease is not treated with proper treatment, it can cause various dangerous complications, and can even threaten the lives of sufferers. Implementation of an expert system to diagnose diabetes using web-based fuzzy mamdani aims to explore the symptoms displayed in the questions - questions in order to be able to diagnose various types of diabetes. This is from a research is a web-based expert system that can detect whether someone has diabetes what type. Based on testing the accuracy of the system, it can be concluded that with the fuzzy mamdani method is more accurate what type of diabetes. By using the PHP programming language with a MySQL database method the expert system used is fuzzy mamdani which is one part of the fuzzy inference system which is useful for drawing conclusions or the best decision in an uncertain problem, the Mamdani fuzzy concept is very flexible and has tolerance for inaccurate data based on language natural.